Surgical treatment of patients with isolated fractures of orbit walls - A. P. Bakushev; K. A. Sivolapov (Oftalʹmologiâ)
Purpose is the optimization of surgical methods in patients with isolated orbital wall fractures.Patients and methods: for patients with isolated orbital wall fractures were used extraoral (n = 46) and infraaxillary (n = 66) surgical approaches. Abolition of defects and deformations using infraaxillary approach was made with a combined endoprosthesis which was developed in the Department of Oral and Maxillofacial Surgery in Novokuznetsk State Institute of Postgradu ate Medicine. The construction is a combination of L-shaped titanium mini-sheet and silicone slab.Results: during the observation the patients who underwent extraoral approaches (n = 46) we have diagnosed following complications: limit of the eyeball movement, diplopy (in case of using metal implants made of porous titanium nickelide and meshed titanium) — 3 (6,5 %) patients; — long-term lymphostas after surgery when using transconjunctive and subciliary approaches — 12 (26,1 %) patients; — ectropion when using infraorbital approach — 2 (4,3 %) patients; — moving of silicone implant with staying by infraorbital rim combined with enophthalmos as a late complication — 3 (6,5 %) patients. In group with infraaxillary approach (n = 66) there were no complications in early postoperative period. Late complications in 2‑6 months in the way of miniplate cutting were found in 5 (7,6 %) cases (in the area of inferior eyelid fold in the scar location), in 1 (1,5 %) cases — enophthalmos within 3 mm. While cutting the miniplate the implants were removed; then there were no any complications.Conclutions: in this study was determined infraaxillary approach was determined the effective method for reconstruction of orbital wall fractures as it removes post-traumatic enophthalmos, limitation of eyebulb movement, diplopy, eversion and lymphostasis of the lower eyelid. The use of infraaxillary approach allows to avoid all these comlications and to reach best clinical and functional results of patients treatment.